ANALISIS YURIDIS PENERAPAN RESTORATIVE JUSTICE TERHADAP TINDAK PIDANA PENCURIAN (Studi Penelitian di Kejaksaan Negeri Lhokseumawe) - Putra, Fhandio Akbar; Husni, Husni; Hidayat, Hidayat (Jurnal Ilmiah Mahasiswa Fakultas Hukum Universitas Malikussaleh, 2024)
This research aims to find out and analyze the process of applying restorative justice to criminal acts of theft and the effectiveness of applying restorative justice to criminal acts of theft. Theft does not only happen to the general public, but can also affect agencies and organizations. This incident caused considerable concern in the community, because they were dissatisfied with the results produced by the criminal justice system. The crime of theft in Indonesian law is classified as a crime related to property in the Criminal Code. It is specifically stated in the second book, Chapter XXII, Articles 362 to 367. The presence of restorative justice is a solution and answer to the anxiety that occurs in society. This research uses empirical research methods and an empirical juridical approach. Data was obtained through field research and library research. Data analysis was carried out qualitatively. Based on research results, the process of applying restorative justice to criminal acts of theft at the Lhokseumawe District Prosecutor's Office is in accordance with Prosecutor's Regulation number 15 of 2020. Throughout 2023, there will be at least two cases resolved with restorative justice at the Lhokseumawe District Prosecutor's Office. Then the effectiveness of the application of restorative justice to criminal acts of theft at the Lhokseumawe District Prosecutor's Office can be said to be quite effective, which can be seen from all the cases that have been carried out using restorative justice which were rejected as measured by the SPDP (Order to Commence Investigation) from the Police.